Incidence of PostOperative Urinary Retention after Pelvic Organ Prolapse Reconstruction - Elisia Elisia; Tyas Priyatini (Indonesian Journal of Obstetrics and Gynecology, 2016)
Abstract Objective: To determine the incidence of post-operative urinary retention after pelvic organ prolapse reconstruction and associated factors. Method: This was a prospective cohort study conducted in Dr. Cipto Mangunkusumo and another associate hospital. We recruited women planned for pelvic organ prolapse reconstruction from April 2013 to April 2015. Inclusion and exclusion criteria were women with pelvic organ prolapse (2nd, 3rd and 4th degree) without prior urinary retention, drugs affecting bladder function, and history of bladder injury. After surgery, urinary catheter was applied for 24 hours. Six hours apart from urinary catheter released, residual urine was measured. Urinary retention was defined as residual urine more than 100 ml. Result: Of 200 subjects, 59 of them (29.5%) classified as having urinary retention. No association found between age, body mass index (BMI), degree of prolapse, degree of cystocele and urinary tract infection toward urinary retention. Total vagina hysterectomy + anterior colporaphy + colpoperineoraphy + sacrospinous fixation and reconstruction duration more than 130 minutes were associated with urinary retention (relative risk (RR) 3.66; 95% CI 2.91-4.60; p